2001
DOI: 10.1038/sj.bjp.0703955
|View full text |Cite
|
Sign up to set email alerts
|

Effects of specific inhibition of cyclo‐oxygenase‐1 and cyclo‐oxygenase‐2 in the rat stomach with normal mucosa and after acid challenge

Abstract: 1 Eects of the cyclo-oxygenase (COX)-1 inhibitor SC-560 and the COX-2 inhibitors rofecoxib and DFU were investigated in the normal stomach and after acid challenge. 2 In healthy rats, neither SC-560 nor rofecoxib (20 mg kg 71 each) given alone damaged the mucosa. Co-treatment with SC-560 and rofecoxib, however, induced severe lesions comparable to indomethacin (20 mg kg 71) whereas co-administration of SC-560 and DFU (20 mg kg 71 each) had no comparable ulcerogenic eect 5 h after dosing. ) given alone were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
87
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 37 publications
18
87
0
1
Order By: Relevance
“…Because transient COX-1 inhibition in control mice that did not receive LPS is not associated with weight loss, our findings suggest that COX-1-generated prostaglandins may serve a protective role during inflammation, such as maintaining gastric mucosal integrity in the face of fasting and stress. This notion is strongly supported by recent studies demonstrating that selective COX-1 inhibition alone does not result in gastric damage, whereas combined COX-1 and COX-2 inhibition, or COX-1 inhibition associated with acid challenge or glucocorticoid administration, does (10,39). The majority of NSAIDs in common clinical use for fever control during infection demonstrate substantial COX-1 inhibitory activity and are likely to cause similar decreases in food intake and body weight maintenance during the recovery phase of illness.…”
Section: Discussionsupporting
confidence: 69%
“…Because transient COX-1 inhibition in control mice that did not receive LPS is not associated with weight loss, our findings suggest that COX-1-generated prostaglandins may serve a protective role during inflammation, such as maintaining gastric mucosal integrity in the face of fasting and stress. This notion is strongly supported by recent studies demonstrating that selective COX-1 inhibition alone does not result in gastric damage, whereas combined COX-1 and COX-2 inhibition, or COX-1 inhibition associated with acid challenge or glucocorticoid administration, does (10,39). The majority of NSAIDs in common clinical use for fever control during infection demonstrate substantial COX-1 inhibitory activity and are likely to cause similar decreases in food intake and body weight maintenance during the recovery phase of illness.…”
Section: Discussionsupporting
confidence: 69%
“…at ASPET Journals on May 10, 2018 jpet.aspetjournals.org gastric ulcer healing in rats (Gretzer et al, 2001;Berenguer et al, 2002;Hatazawa et al, 2007), whereas the dose of valdecoxib has been shown to produce a selective COX-2 inhibition in rat (Gierse et al, 2005;Ahmad et al, 2009). For these reasons, the above doses were used in our subsequent experimental procedures.…”
Section: Nsaid-activated Gene and Gastric Ulcer Healing 143mentioning
confidence: 99%
“…28 -30 Ketorolac (2 mg/kg) preferentially inhibits COX-1, 31 whereas rofecoxib (2 or 20 mg/kg) selectively blocks COX-2. 32 Determination of NOS-II, COX-1, COX-2, and ␤-Actin mRNA Total RNA (50 g) from the heart, lung, and liver was extracted, and the abundance of NOS II mRNA, COX-1 mRNA, and COX-2 mRNA was semi-quantitated and related to ␤-actin mRNA (1 g) by specific RNase protection assay as described. 8,33 Determination of Nitrate/Nitrite, PGE 2 , and 6-Keto PGF 1␣ Nitrate/nitrite concentrations and concentrations of PGE 2 and 6-keto prostaglandinF 1␣ in plasma and liver were determined using commercially available assay kits (Cayman Chemical).…”
Section: Animal Experimentsmentioning
confidence: 99%